Oral rehabilitation in a child with early childhood caries: a case report - Fernanda Miori PASCON; Carolina STEINER-OLIVEIRA; Priscila Alves GIOVANI; Regina Maria PUPPIN-RONTANI; Kamila Rosamilia KANTOVITZ (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT The aim of the current study is to present a treatment approach in a case of severe early childhood caries (ECC). A 5-year-old girl was referred to the Pediatric Dentistry Division with multiple premature tooth loss, masticatory difficulties, prolonged breast-feeding, and low quality of life, who was diagnosed with severe ECC. A three-phased treatment plan was implemented: 1. Disease control - consisting of behavioral changes in oral hygiene habits, diet guidance, professional biofilm removal followed by fluoride application and temporary restorations; 2. Infection control - teeth extractions and pulpotomy; and 3. Functional rehabilitation - direct and semi-indirect resin restorations, a removable partial and total prostheses in the lower and upper jaws, respectively. In conclusion, the proposed multidisciplinary approach resulted in a positive impact on the patient's nutrition and growth, speech production, communication, self-image, and social functioning leading to an improved quality of life.